Integrating the Perspective of Hakiki Justice for Women in Gender Research Methods: An Analysis of Nur Rofiah's Interpretive Thinking - Muhammad Hidayat; Sri Ayu Agustina; Umi Barokah; Teguh Arafah Julianto (The Ulama Cadre Education Program of Great Mosques of Istiqlal (PKUMI), 2025)
This study explores the integration of the hakiki justice for women perspective into Islamic gender research methodology based on Nur Rofiah’s Qur’anic interpretation. Using a qualitative library research approach, it examines the concept of hakiki justice emphasizing substantive equality, humanity, and welfare. Nur Rofiah asserts that Qur’anic interpretation must be grounded in universal moral values such as piety, justice, and compassion. In research methodology, hakiki justice serves as an epistemological foundation recognizing women’s biological and social experiences as valid sources of knowledge. Through two main pillars, the Qur’an as a system of values and as a historical process toward justice, Rofiah develops a contextual, humanistic, and transformative approach. The findings reveal that integrating hakiki justice for women reconstructs Islamic research paradigms toward a more just, inclusive, and gender-equitable knowledge framework.